TEST PHYTOCHEMICAL, TOXICITY AND ANTIBACTERIAL ACTIVITY FRACTION LEAF EXTRACT VARIOUS MAHANG (M acarang apruinosa (Miq.) Mull. Arg.) AGAINST Escherichia coli AND Staphylococcus aureus - Mustafidah -; Chairul Saleh; Alimuddin - (PROSIDING SEMINAR KIMIA, 2014)
Phytochemical, to xicity and antibacterial act ivity tests of total extract, fractions of n-heksana, ethyl acetate and ethanol-water fro m mahang leaf (Macaranga pruinosa (M.) M. A.) fro m KRUS (Kebun Raya Unmul Samarinda), East Kalimantan has been carried out. Based on the secondary metabolites phytochemical test of the (Macaranga pruinosa (M.) M. A.) leaf show that total extract is contain alkaloid and steroid. n-hexane fraction is contain alkaloid and steroid. Ethyl acetate fract ion is contain steroid. Ethanol-water fract ion is contain alkaloid and phenolic. Brine shrimp lethality test values obtained Lethal Concentration 50 % (LC 50 ) total extract 27,5036 ppm , n-heksana fraction 12,0773 pp m, ethyl acetate fraction 23719,2305 ppm and ethanol-water fraction 250,0384 ppm. Antibacteria act ivity test of extracts for Staphylococcus aureus bacteria (positive Gram) and Escherichia coli (negative Gram) minimum inhibitor consentration of 0-1 % (b/v) fro m ext ract fractions of n-heksana and fractions ethyl acetate for Staphylococcus aureus bacteria and fractions ethyl acetate for Escherichia coli bacteria.